2001
DOI: 10.1034/j.1398-9995.2001.056005442.x
|View full text |Cite
|
Sign up to set email alerts
|

Basophil activation during pollen season in patients monosensitized to grass pollens

Abstract: Basotest can therefore be used as a diagnostic test during the pollen season, but the allergen exposure needs to be characterized if quantitative studies are performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 13 publications
0
24
1
2
Order By: Relevance
“…Many of these studies have been reviewed recently [8,9,10]. Herewith, tables 1, 2, 3, 4, 5, 6, 7summarize the results of validated clinical studies performed with various allergens such as inhalant allergens [25,26,27,28,29,30,31,32,33] (table 1), hymenoptera venoms [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56] (table 2), latex [57,58,59,60,61,62,63] (table 3), food [64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80] (table 4) and drugs [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,…”
Section: Clinical Issues In the Diagnostic Use Of Batmentioning
confidence: 99%
“…Many of these studies have been reviewed recently [8,9,10]. Herewith, tables 1, 2, 3, 4, 5, 6, 7summarize the results of validated clinical studies performed with various allergens such as inhalant allergens [25,26,27,28,29,30,31,32,33] (table 1), hymenoptera venoms [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56] (table 2), latex [57,58,59,60,61,62,63] (table 3), food [64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80] (table 4) and drugs [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,…”
Section: Clinical Issues In the Diagnostic Use Of Batmentioning
confidence: 99%
“…Acquisition was performed on 1,000 cells for each sample and results are given as the percentage of basophils (IgE-positive cells) expressing gp53 (CD63). The theoretical cut-off of 15% of IgE-positive cells expressing CD63 in at least one of the concentrations was first used according to previous results and the notice of the kit [7, 10]. …”
Section: Methodsmentioning
confidence: 99%
“…The Basotest ® (CD63-based flow-cytometric cellular allergen stimulation test) could be an alternative [15]. Based upon the expression of CD63 (gp53) in the presence of allergens, it has been proved to establish the diagnosis of IgE dependent allergies including cypress pollen, house dust mite, β-lactam, muscle relaxant and venom allergies [7, 8, 9, 10, 11, 16]. In this study, we evaluated the reliability of Basotest in the diagnosis of latex allergy and attempted to establish a threshold value for this test.…”
Section: Introductionmentioning
confidence: 99%
“…Dahlen et al 20 performed bronchial provocation and BAT and confirmed that a BAT result is an objective marker of respiratory tract sensitivity to an allergen in patients with stable allergic asthma and may replace specific bronchial provocation. 20 In comparison to NPT, the advantages of BAT, apart from saving the patient from exposition to an incidence of allergic symptoms during the test, include the possibility of diagnosis regardless of the pollination season 21,22 and no requirement to discontinue the use of many symptom--relief medications. 23 In our study, NPT could not be performed in just 1 patient because of exacerbation of rhinitis symptoms at baseline.…”
Section: 12mentioning
confidence: 99%